DFT Modeling of Novel Donor‐Acceptor (D‐A) Molecules Incorporating 3‐hexylthiophene (3HT) for Bulk Heterojunction Solar Cells. Issue 31 (2nd November 2017) - Khlaifia, Dalila; Massuyeau, Florian; Ewels, Christopher P.; Duvail, Jean‐Luc; Faulques, Eric; Alimi, Kamel
Abstract: As potential donor materials for organic photovoltaic (OPV) devices, six conjugated small molecules with donor‐acceptor configuration based on 3‐hexylthiophene monomer (3HT) were designed and studied by means of density functional theory (DFT) and time‐dependent DFT. Their geometric structure, electronic and optical properties were investigated at PBE0/6‐31G(d) level. Amongst these times we selected the two most promising molecules (3HT)2 ‐DPP)n=1 (1 ) and (3HT)2 ‐DTP)n=1 (4 ), containing respectively the diketopyrrolo[3, 4‐c]‐pyrrole‐1, 4‐dione (DPP) and 7, 8‐dihydroxy‐thieno[3, 4‐b]pyrazine (DTP) as acceptor units coupled with a core donor (3HT dimer (3HT)2 ), showing a novel strong absorption band in the visible range and spatially delocalized HOMO and LUMO states. These have been exploited as electron donors for a heterojunction with [6, 6]‐phenyl‐C61 ‐butyric acid methyl ester (PC61 BM) as the electron acceptor. The charge transfer dynamics, including intermolecular charge transfer (inter‐CT) and recombination (inter‐CR) rates, were examined. The results reveal that the ratio k int e r - C T / k int e r - C R for the (3HT)2 ‐DTP)n=1 /PC61 BM heterojunction is more than 10 9 times higher than that of the (3HT)2 ‐DPP)n=1 /PC61 BM, suggesting that (3HT)2 ‐DTP)n=1 is a promising candidate for OPVs. Abstract : As potential donor materials for organic photovoltaic devices (OPV), six conjugated molecules with donor‐acceptor configuration based on 3‐hexylthiophene were studied with density functional theory (DFT) and time‐dependent DFT. Two molecules showing a novel absorption band in the visible range and spatially delocalized HOMO and LUMO states have been exploited as electron donors for a heterojunction with [6, 6]‐phenyl‐C61 ‐butyric acid methyl ester as the electron acceptor. The charge transfer dynamics were examined for the goal to choose a promising candidate for OPVs.